This action might not be possible to undo. Are you sure you want to continue?

# Practical yield, price, duration and convexity

approximations

D. L. Chertok

†

November 7, 2012

Abstract

Practical techniques for approximating yield given the price and price

given the yield are described. Duration and convexity estimations given

prices and yields at three observation points are presented. Such approxi-

mations are useful when computing prices and yields from their values at

nearby points and generating additional data for scenario analysis.

1 Price approximation given the yield and yield

approximation given the price.

The duration-convexity (second order) approximation of price given the yield of

a security is well-known[2]. The inverse relationship, i.e., the approximation or

yield given the price, is found in text books less often, however, it can be just

as useful for practical purposes.

Suppose that we know the yield of a security or portfolio of securities y

0

corresponding to the price p

0

. By Taylor expansion [1], (approximated) price p

corresponding to (known) yield y can be computed as

p(y) ≈ p

0

+

dp(y)

dy

¸

¸

¸

¸

y=y0

(y −y

0

) +

1

2

d

2

p(y)

dy

2

¸

¸

¸

¸

y=y0

(y −y

0

)

2

, (1)

or, in terms of duration and convexity,

p(y) ≈ p

0

_

1 −D(y

0

)(y −y

0

) +

1

2

C(y

0

)(y −y

0

)

2

_

, (2)

D(y

0

) = −

1

p

0

dp(y)

dy

¸

¸

¸

¸

y=y0

, (3)

C(y

0

) =

1

p

0

d

2

p(y)

dy

2

¸

¸

¸

¸

y=y0

, (4)

where:

†

D. L. Chertok, Ph. D., CFA, (daniel chertok@hotmail.com) is a quantitative investment

professional in Chicago, IL.

1

D(y

0

) - duration at y

0

, provided it is not undeﬁned,

C(y

0

) - convexity at y

0

, provided it is not undeﬁned.

Conversely, (approximated) yield y corresponding to (known) price p can be

computed as

y(p) ≈ y

0

+

dy(p)

dp

¸

¸

¸

¸

p=p0

(p −p

0

) +

1

2

d

2

y(p)

dp

2

¸

¸

¸

¸

p=p0

(p −p

0

)

2

. (5)

or, in terms of duration and convexity,

y(p) ≈ y

0

−

p −p

0

p

0

D(y

0

)

+

1

2

(p −p

0

)

2

C(y

0

)

p

2

0

D

3

(y

0

)

. (6)

See Appendix A for the derivation of (6).

2 Estimating approximation parameters from

observed data points

It is sometimes convenient to approximate the eﬀective duration and convexity

of a bond (or a more complex security) rather than calculate those quantities

directly. The formulas below provide a means to perform such an approximation

using prices and yields known at three data points.

Suppose that two data points (y

1

, p

1

) and (y

2

, p

2

) are known in the neigh-

borhood of (y

0

, p

0

). To the second degree of accuracy, from (2) we get

p

(y

0

) +

1

2

∆y

1

p

(y

0

) =

∆p

1

∆y

1

, (7)

p

(y

0

) +

1

2

∆y

2

p

(y

0

) =

∆p

2

∆y

2

, (8)

where:

p

(y

0

) =

dp

dy

¸

¸

¸

¸

y=y0

, provided it is deﬁned,

p

(y

0

) =

d

2

p

dy

2

¸

¸

¸

¸

y=y0

, provided it is deﬁned,

∆p

i

= p

i

−p

0

, i = 1, 2 ,

∆y

i

= y

i

−y

0

, i = 1, 2 .

This is a linear system of two equations in two unknowns, p

(y

0

) and p

(y

0

).

2

The solution is given by

p

(y

0

) =

∆p

1

(∆y

2

)

2

−∆p

2

(∆y

1

)

2

∆y

1

∆y

2

(y

2

−y

1

)

, (9)

p

(y

0

) =

2(∆y

1

∆p

2

−∆y

2

∆p

1

)

∆y

1

∆y

2

(y

2

−y

1

)

. (10)

Accordingly, for duration D and convexity C:

D(y

0

) = −

p

(y

0

)

p

0

= −

∆p

1

(∆y

2

)

2

−∆p

2

(∆y

1

)

2

∆y

1

∆y

2

(y

2

−y

1

)p

0

, (11)

C(y

0

) =

p

(y

0

)

p

0

=

2(∆y

1

∆p

2

−∆y

2

∆p

1

)

∆y

1

∆y

2

(y

2

−y

1

)p

0

. (12)

See Appendix B for the derivation of (9) - (12).

3 Example

This example illustrates the approximation described above for a 1.5% 10-year

US Treasury bond

1

with a price of 99.5 (per $100 notional) currently yielding

1.5542%.

Table 1: Worked example of price, duration and convexity approximations.

Scenario Price Yield,

%

Eﬀective

Dura-

tion,

Excel

Eﬀective

Con-

vexity,

Excel

Eﬀective

Dura-

tion,

approx.

Eﬀective

Con-

vexity,

approx.

Base 99.5000 1.5542 -9.2494 94.0938 9.2494 94.0938

- 100 bp 99.5921 1.5442

+ 100 bp 99.4080 1.5642

1

Idealized, i.e., without accounting for holidays or weekends.

3

Appendix A Derivation of the yield approxi-

mation in terms of duration and

convexity

Applying the usual reasoning for inverse functions

2

to (3), we get

dy

dp

=

1

dp

dy

= −

1

pD

, (A.1)

d

2

y

dp

2

= −

d

dp

_

1

pD

_

=

D −p

dD

dp

p

2

. (A.2)

By the chain rule,

dD

dp

=

dD

dy

dy

dp

=

dD

dy

_

−

1

pD

_

, (A.3)

dD

dy

= −

dp

dy

p

= −

d

2

p

dy

2

p

+

_

dp

dy

_

2

p

2

= −C(y) + D

2

(y) , (A.4)

hence

dD

dp

=

D

2

−C

pD

, (A.5)

and

d

2

y

dp

2

=

D −

p

pD

_

D

2

−C

_

p

2

D

2

=

C

p

2

D

3

, (A.6)

yielding, in terms of duration and convexity,

y(p) ≈ y(p

0

) −

p −p

0

p

0

D(y

0

)

+

1

2

(p −p

0

)

2

C(y

0

)

p

2

0

D

3

(y

0

)

. (A.7)

Appendix B Derivation of duration and con-

vexity approximations

Recall that (9) - (10) is a 2x2 system of linear equations in p

(y

0

) and p

(y

0

):

p

(y

0

) =

∆p

1

(∆y

2

)

2

−∆p

2

(∆y

1

)

2

∆y

1

∆y

2

(y

2

−y

1

)

, (B.1)

p

(y

0

) =

2(∆y

1

∆p

2

−∆y

2

∆p

1

)

∆y

1

∆y

2

(y

2

−y

1

)

. (B.2)

2

Yield as a function of price for a ”reasonable” ﬁxed income security is (at least) contin-

uously diﬀerentiable. The derivative of yield with respect to price can only be zero in trivial

cases, so we can diﬀerentiate the inverse function.

4

Computing the determinants, we obtain:

∆ =

¸

¸

¸

¸

1 0.5∆y

1

1 0.5∆y

2

¸

¸

¸

¸

= 0.5(∆y

2

−∆y

1

)

= 0.5(y

2

−y

0

−y

1

+ y

0

) = 0.5(y

2

−y

1

) = 0 , (B.3)

∆

p

=

¸

¸

¸

¸

¸

∆p1

∆y1

0.5∆y

1

∆p2

∆y2

0.5∆y

2

¸

¸

¸

¸

¸

= 0.5

∆p

1

(∆y

2

)

2

−∆p

2

(∆y

1

)

2

∆y

1

∆y

2

, (B.4)

∆

p

=

¸

¸

¸

¸

¸

1

∆p1

∆y1

1

∆p2

∆y2

¸

¸

¸

¸

¸

=

∆p

2

∆y

1

−∆p

1

∆y

2

∆y

1

∆y

2

. (B.5)

Hence [3],

p

(y

0

) =

∆

p

∆

=

∆p

1

(∆y

2

)

2

−∆p

2

(∆y

1

)

2

∆y

1

∆y

2

(y

2

−y

1

)

, (B.6)

p

(y

0

) =

∆

p

∆

=

2(∆p

2

∆y

1

−∆p

1

∆y

2

)

∆y

1

∆y

2

(y

2

−y

1

)

, (B.7)

Dy

0

= −

p

(y

0

)

p

0

= −

∆p

1

(∆y

2

)

2

−∆p

2

(∆y

1

)

2

∆y

1

∆y

2

(y

2

−y

1

)p

0

, (B.8)

Cy

0

=

p

(y

0

)

p

0

=

2(∆p

2

∆y

1

−∆p

1

∆y

2

)

∆y

1

∆y

2

(y

2

−y

1

)p

0

. (B.9)

References

[1] Abramowitz, M. and Stegun, I. Handbook of Mathematical Functions with

Formulas, Graphs, and Mathematical Tables. Dover Publications, 1965.

[2] F. Fabozzi. The Handbook of Fixed Income Securities. McGraw-Hill, 7th

edition, 2005.

[3] Strang, G. Linear Algebra and Its Applications. Brooks Cole, 4th edition,

2005.

5